So what you do is
make into ax^2+bx+c=0 form
add-9/2 to both sides
y^2-2y+9/2=0
now we use the quadratice formula which is
x=
![\frac{-b+/- \sqrt{b^{2}-4ac} }{2a}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-b%2B%2F-%20%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%20%7D%7B2a%7D%20)
ax^2+bx+c=0
1y^2-2y+9/2
a=1
b=-2
c=9/2
subsitute
x=
![\frac{-(-2)+/- \sqrt{(-2)^{2}-4(1)(9/2)} }{2(1)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-%28-2%29%2B%2F-%20%5Csqrt%7B%28-2%29%5E%7B2%7D-4%281%29%289%2F2%29%7D%20%7D%7B2%281%29%7D%20)
x=
![\frac{2+/- \sqrt{4-(36/2)} }{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%2B%2F-%20%5Csqrt%7B4-%2836%2F2%29%7D%20%7D%7B2%7D%20)
x=
![\frac{2+/- \sqrt{4-(18)} }{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%2B%2F-%20%5Csqrt%7B4-%2818%29%7D%20%7D%7B2%7D%20)
x=
![\frac{2+/- \sqrt{-14} }{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%2B%2F-%20%5Csqrt%7B-14%7D%20%7D%7B2%7D%20)
x=
![\frac{2+/- \sqrt{-14} }{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%2B%2F-%20%5Csqrt%7B-14%7D%20%7D%7B2%7D%20)
x=
![1+/- \frac{\sqrt{-14} }{2}](https://tex.z-dn.net/?f=%201%2B%2F-%20%5Cfrac%7B%5Csqrt%7B-14%7D%20%7D%7B2%7D%20)
x=
![1+/- \frac{\sqrt{14} \sqrt{-1}}{2}](https://tex.z-dn.net/?f=%201%2B%2F-%20%5Cfrac%7B%5Csqrt%7B14%7D%20%5Csqrt%7B-1%7D%7D%7B2%7D%20)
x=
![1+/- \frac{\sqrt{14} i }{2}](https://tex.z-dn.net/?f=%201%2B%2F-%20%5Cfrac%7B%5Csqrt%7B14%7D%20i%20%7D%7B2%7D%20)
x=
![1+/- \frac{ i \sqrt{14} }{2}](https://tex.z-dn.net/?f=%201%2B%2F-%20%5Cfrac%7B%20i%20%5Csqrt%7B14%7D%20%7D%7B2%7D%20)
answer is C
Answer:
b
Step-by-step explanation:
because a ste and leaf plot have the value for 2
The quotient rule is
d(u/v) = (u dv - v du) / u2
d(u/v) can written as
d( u (1/v) )
Using the product rule and chain rule
d( u (1/v)) = u d(1/v) + (1/v) du
= u (-1/v2) dv + (!/v) du
= (u dv - v du) / u2
Answer:
My answer is 43 its that rigth
Answer:
a square backyard with width (x - 9)
Step-by-step explanation:
x²−18x + 81 = x² - (2 x 9) x + 9² = (x - 9)²
width = area / length = (x - 9)² / (x - 9) = x - 9
Length = width
This is a square backyard